Electoral Dynamics and Islamic Politics: The Role of Religious Organizations in West Java's Regional Head Elections - Zidnal Falah (Journal of Political Innovation and Analysis, 2025)
This study examines the role of religious organizations in shaping electoral dynamics in West Java's regional head elections, particularly focusing on how Islamic organizations, such as Nahdlatul Ulama (NU) and Muhammadiyah, influence voter behavior and political outcomes. Despite the overwhelming Muslim majority in Indonesia, Islamic political parties have seen a consistent decline in electoral support, a phenomenon that this research explores through a case study of West Java a province with significant religious and political importance. The study employs a qualitative case study approach, utilizing interviews with key stakeholders and secondary data such as electoral statistics and organizational documents. The research identifies three main mechanisms through which religious organizations engage in electoral politics: resource mobilization, strategic framing, and social network activation. Findings reveal that NU's influence operates through structural mobilization, while Muhammadiyah engages in strategic ambiguity, focusing on individual participation rather than organizational endorsements. The study also finds that religious authority in West Java has declined, with younger voters increasingly making independent electoral choices. The implications of this research highlight the evolving role of religious organizations in Indonesia's electoral politics and suggest the need for political practitioners to understand the complex interplay between religion and politics in a diverse society.